2013
DOI: 10.1586/14737159.2014.864238
|View full text |Cite
|
Sign up to set email alerts
|

The value of procalcitonin measurement in localized skin and skin structure infection, diabetic foot infections, septic arthritis and osteomyelitis

Abstract: Serum procalcitonin (PCT) is an established diagnostic marker for severe or systemic bacterial infections such as pneumonia, sepsis and septic shock. Data regarding the role of PCT in localized infections without systemic inflammatory response syndrome are scarce. The aim of this review is to assess the value of PCT measurements in localized infections such as skin and skin structure infections, diabetic foot infections, septic arthritis (SA) and osteomyelitis. It appears that serum PCT is unlikely to change t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…However, in some cases, there are difficulties in using these markers as indicators of diagnosis and treatment due to their low sensitivity and specificity5. A recent study reported the value of procalcitonin in bullous impetigo, staphylococcal scaled skin syndrome, localized skin infection, diabetic foot infection, septic arthritis and osteomyelitis67. In addition, procalcitonin may be a useful tool for the initial diagnosis and monitoring of cutaneous infection or cutaneous soft tissue infection8.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some cases, there are difficulties in using these markers as indicators of diagnosis and treatment due to their low sensitivity and specificity5. A recent study reported the value of procalcitonin in bullous impetigo, staphylococcal scaled skin syndrome, localized skin infection, diabetic foot infection, septic arthritis and osteomyelitis67. In addition, procalcitonin may be a useful tool for the initial diagnosis and monitoring of cutaneous infection or cutaneous soft tissue infection8.…”
Section: Introductionmentioning
confidence: 99%
“…A very recent study looked at the value of PCT and interleukin‐6 in patients with bullous impetigo and staphylococcal scalded skin syndrome . Finally, a review paper discussed the value of PCT in localized skin and skin structure infection, diabetic foot infections, septic arthritis and osteomyelitis …”
Section: Introductionmentioning
confidence: 99%
“…23 Finally, a review paper discussed the value of PCT in localized skin and skin structure infection, diabetic foot infections, septic arthritis and osteomyelitis. 24 The aim of our study was to investigate the diagnostic value of PCT levels as compared with CRP levels and WBC counts in a consecutive at-risk population of patients presenting with either erysipelas or DVT of the lower limb to the ED of a tertiary care hospital in Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…The use of serum procalcitonin has been suggested as a valuable marker for the severity and mortality in sepsis 10,11 and possibly acute osteomyelitis. 15 Diagnostic imaging tools to assess bone infection include MRI and bone scans. 13 Other investigators have demonstrated the superiority of CRP over procalcitonin for detecting infection in deep orthopaedic implants.…”
Section: Chronic Wounds With Exposed Implantsmentioning
confidence: 99%